Transparency Under Trump: Policy and Prospects. (4th March 2019) - Ellington, Thomas C.
Abstract : Donald Trump came into office succeeding a President who had a strong rhetorical commitment to transparency, having promised to have "the most transparent administration in history." Indeed, as President, Barack Obama took concrete steps toward greater openness. However, most observers hold that the Obama presidency fell short of its promise on transparency, given its continued resorting to state secrets privilege in civil cases and its aggressive pursuit and prosecution of public-interest leakers. Trump, meanwhile, lacks even the rhetorical commitment to transparency that Obama had, and he has, at times, been openly hostile to the idea. This article examines the actions taken during the early months of the Trump administration and their significance for transparency in the United States. Although Trump is ill-disposed toward transparency and early signs are worrisome for transparency advocates, that disposition has not yet translated into major policy initiatives.